Synthesis of ZnO/CuO Composite by The Electrochemical Method in The Acetat Acid Solution - Adrian Nur; Jundi Rofi’uddien; Muhammad Abdul Basir; Nazriati Nazriati; Fauziatul Fajaroh (Equilibrium Journal of Chemical Engineering, 2018)
The metal oxide composite is used to the microelectronic circuit, piezoelectric, fuel cell, sensor, catalyst, coating for preventing corrosion, and solar cell. The ZnO/CuO is one of the metal oxide composites. The combination of ZnO and CuO is the potential composite used to the catalyst and the anti-bacterial agent. The method used in this research was the electrochemical method in the acetate acid solution. The acetate acid solution used in this research is cheaper than the succinite acid used in the previous research. The electrochemical method has advantages due the easy to control and cheap. The composite resulted was analyzed by the XRD and the FTIR. The aims of this analysis are to know the crystallite phase, structure, and the functional groups of the particle resulted. The analysis showed that the ZnO-CuO composite can be resulted by the electrochemical method.